2010
DOI: 10.1371/journal.pone.0010438
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-Converting Enzyme Gln1069Arg Mutation Impairs Trafficking to the Cell Surface Resulting in Selective Denaturation of the C-Domain

Abstract: BackgroundAngiotensin-converting enzyme (ACE; Kininase II; CD143) hydrolyzes small peptides such as angiotensin I, bradykinin, substance P, LH-RH and several others and thus plays a key role in blood pressure regulation and vascular remodeling. Complete absence of ACE in humans leads to renal tubular dysgenesis (RTD), a severe disorder of renal tubule development characterized by persistent fetal anuria and perinatal death.Methodology/Principal FindingsPatient with RTD in Lisbon, Portugal, maintained by perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 71 publications
2
44
1
Order By: Relevance
“…All except those previously reported in four families [Danilov et al, 2010;Gribouval et al, 2005;Schreiber et al, 2010;Uematsu et al, 2009] were novel. Mutations were present in the homozygous state in 15 families, in the compound heterozygous state in 13, whereas only one heterozygous ACE mutation was identified in three families.…”
Section: Angiotensin-converting Enzyme Acementioning
confidence: 80%
See 2 more Smart Citations
“…All except those previously reported in four families [Danilov et al, 2010;Gribouval et al, 2005;Schreiber et al, 2010;Uematsu et al, 2009] were novel. Mutations were present in the homozygous state in 15 families, in the compound heterozygous state in 13, whereas only one heterozygous ACE mutation was identified in three families.…”
Section: Angiotensin-converting Enzyme Acementioning
confidence: 80%
“…Mutations in the RAS genes are reported in 15 families [Bacchetta et al, 2007;Ben Amar et al, 2007;Danilov et al, 2010;Gribouval et al, 2005;Michaud et al, 2011;Schreiber et al, 2010;Uematsu et al, 2006Uematsu et al, , 2009Zingg-Schenk et al, 2008] and new sequence changes identified in our laboratory in 33 families are presented in Table 1. New mutations were identified by direct sequence analysis as described previously [Gribouval et al, 2005].…”
Section: Mutations In the Ras Genesmentioning
confidence: 86%
See 1 more Smart Citation
“…This quality control mechanism ensures that only properly folded proteins are delivered to their final destinations, thereby retaining and degrading misfolded polypeptides without preventing the export of properly folded proteins. However, several human diseaserelated mutant proteins with varying degrees of activity are retained in the ER, such as Duox2, CFTR, aquaporin-2, angiotensin I-converting enzyme, the V2 vasopressin receptor, the sulfonylurea receptor, the HERG K + channel, the melanocortin-4 receptor and the luteinizing hormone G proteincoupled receptor (Danilov et al, 2010;Grasberger et al, 2007;Li et al, 1993;Meimaridou et al, 2011;Morello et al, 2000;Newton et al, 2011;Partridge et al, 2001;Tamarappoo and Verkman, 1998;Zhou et al, 1999). Most ITD-causing NIS mutants are, like WT NIS, targeted to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one drug of this class, bortezomib, is being used for treatment of some hematologic malignancies. Proteasomal inhibitors have also been reported to rescue targeting to the plasma membrane and function of some proteasomally degraded mutants associated with other diseases (45)(46)(47)(48). Other inhibitors of the proteasome that may have reduced secondary effects (49,50) are being developed, and they may eventually allow chronic application to prevent or ameliorate disease (like cataracts).…”
Section: Discussionmentioning
confidence: 99%